Comprehensive analysis to drive the energy retrofit of a neighborhood by optimizing the solar energy exploitation – An Italian case study. (10th September 2021) - Ascione, Fabrizio; Bianco, Nicola; Mauro, Gerardo Maria; Napolitano, Davide Ferdinando; Vanoli, Giuseppe Peter
Abstract: Buildings account for around one third of World energy consumption and polluting emissions, thus their energy retrofit is crucial aiming at reducing the human impact on the environment. In this context, worldwide, public grant policies and stringent requirements have been adopted to promote energy efficiency in the building sector. This study proposes a comprehensive analysis to drive the energy retrofit of building neighborhoods by examining energy efficiency measures involving envelope components, heating, ventilating and air conditioning systems, photovoltaics. The effects of the creation of a local energy community that shares the photovoltaic production are taken into account too. Finally, the Italian "Superbonus 110%" public grant policy is considered, and some insights are given. More in detail, the analysis aims at minimizing at the same time the primary energy consumption and the global cost, satisfying both the public and the private stakeholders. It makes use of different software: CADMapper® and SketchUp® for modeling the geometry of the neighborhood; DesignBuilder® for realizing the first raw energy model; EnergyPlus to refine the energy model and to perform dynamic energy simulations; MATLAB® to post-process the results of the simulations. As case study, an existing neighborhood located in Naples (Italy) is investigated and three suboptimal solutions are proposed: nZEB solution, cost-optimal solution and utopia solution. Sensible reductions in energy consumption and global cost can be achieved in presence of public grants, i.e., up to 69.2 kWh/m 2 a and 153.6 €/m 2, respectively. Graphical abstract: Image 1 Highlights: A comprehensive analysis for the energy retrofit of neighborhoods is conducted. Energy retrofit measures affect envelopes, HVAC systems and photovoltaics. 3 optimal solutions are proposed: nZEB, cost-optimal, utopia (tradeoff). The Italian "Superbonus 110%" public grant policy is taken into account. A neighborhood in Naples (Italy) is examined. High potential benefits are achieved.